Strumenti e strategie della comunicazione scritta in Europa fra Medioevo ed Età Moderna - Doni Garfagnini, Manuela (Biblioteca di storia, 2017)
The theme of written communication is the red thread linking all the historical essays collected here. However, it does not concern the study of the specific channel or of its history, but rather the methods used to create writings or editorial initiatives, for the achievement of specific objectives. Writing and publishing are the two poles around which the various contributions revolve, whose features respond to a project aimed at probing the intention underlying the work of authors and publishers engaged in transmitting not only news, but above all contents: from religious to cultural, literary, scientific, political, or propaganda. The aim is the one of trying to read European History through a lens supporting the trends of the contemporary world, reflecting opinions, strategies and communication methods developed in different eras, so as to arouse interest around aspects of past realities which reveal new historical processes .